Total Quality Management Implementation and Organizational Development Among Indian Industries: A Study on the Implementation of Total Quality Management in Indian Industries (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In this paper we present about total quality managementimplementation and organizational development among Indian industries. Thereare many draw near in the business domain in order to attain and exceed thequality prospect of the clients. For this, most companies integrate all quality-relatedprocesses and functions together and control it from a central point. As itsname suggests, Total Quality Management takes the whole thing connected toexcellence quality into deliberation, including the company processes, processoutcomes and human resources.